A study to assess the knowledge regarding breast cancer and practices of breast self-examination among women in urban area - Singh, Rakesh; Turuk, Alka (International Journal Of Community Medicine And Public Health, 2017)
Background: Out of all cancers, breast cancer only is responsible for 1.5 lakh cases (10%) of cancer burden in India by 2016. The present study was carried out among women in an urban area with objective to assess knowledge of women in age group 20-60 years regarding causes and risk factors of breast cancer and their practice regarding breast self-examination. An association between the socio-demographic variables and knowledge of women regarding breast cancer and breast self-examination was sought for and an attempt was made to demonstrate individually to each woman included in the study, the correct method of performing BSE. Methods: A community based cross sectional study was conducted. Total 100 subjects were selected by multistage sampling technique. Structured questionnaire were used to test their knowledge about breast cancer and practice regarding BSE. Results: Out of 100 women, 58% had knowledge that breast cancer was the most prevalent cancer among women, 52% knew what breast self-examination is and 28% were practicing breast self-examination. Conclusions: There is a need for developing health education programs about symptoms and early signs of breast cancer with emphasis on the importance of early breast cancer detection. Breast self-examination should be encouraged. The health education programs and mass media education should be targeted towards females in the age group between 20 years and above, ideally those 35 years of age and above. Further research regarding knowledge and practice of women towards breast cancer is recommended.